Status and Prospects of Freight Transportation in the Russian Federation - Alexey Yuryevich Smirnov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the article the tendencies of development of freight turnover of various types of transport are considered. The main factors determining the existing trends are revealed. Mathematical models for forecasting freight turnover are presented.